Effects of waste coffee grounds on the mechanical properties, flame retardancy and toxic gas production of epoxy composites. (December 2022) - Yang, Wenmu; Chang, Wenkai; Zhang, Jin; Yeoh, Guan Heng; Boyer, Cyrille; Wang, Chun H.
Graphical abstract: Highlights: Waste coffee grounds improve the flame retardancy and reduce toxic gases emissions of epoxy composites. Reducing the size of coffee grounds further improves the flame. Reduced size coffee grounds can achieve similar peak heat release rate reduction as commonly used inorganic flame retardants. A micro mechanical finite element model has been developed to predict the tensile strength of particle/epoxy composites. Abstract: Waste coffee grounds, a biomaterial with high carbon content, have been suggested as a non-toxic organic flame retardant due to their high char forming and radical scavenging properties. Herein, investigations are conducted on the effects of waste coffee grounds, especially their concentration and particle size, on the mechanical properties, flame retardancy, toxic gas production of epoxy composites. Results reveal that reducing average size of the waste coffee grounds from 46 µm to 16 µm, using freeze-milling or filtering, can reduce peak heat release rate and total heat release of their epoxy composites by 52.0% and 33.7% respectively, exceeding the effectiveness of other bio-based flame retardants such as chitosan, lignin and seashell. More importantly, the fine coffee grounds can achieve the same performance as aluminium trihydrates, the most widely used non-bio flame retardant. Furthermore, the burning rates and emissions of toxic gas have also been greatly reduced, almost entirely suppressing the highly toxic NO2 gas. The findings provide new insights into the effect of particle size of waste coffee grounds on both the mechanical properties and flame retardancy performnance of epoxy composites.